2008
DOI: 10.1590/s1413-70542008000200008
|View full text |Cite
|
Sign up to set email alerts
|

Enraizamento de estacas de Ginkgo biloba tratadas com ácido indolbutírico e ácido bórico

Abstract: RESUMOObjetivou-se neste trabalho estudar o efeito do ácido indolbutírico (AIB) e do ácido bórico (B) no enraizamento de estacas de Ginkgo biloba. Em estacas com duas folhas, medindo 15 cm de comprimento foram provocadas duas lesões na base de aproximadamente 2 cm, expondo o câmbio e procedeu-se à imersão por 10 segundos no tratamento correspondente, AIB (0, 1000, 2000 e 3000 mg L Termos para indexação: Auxinas, Ginkgo biloba, propagação vegetativa. ABSTRACTThe aim of the work was to study the effect of indolb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
(11 reference statements)
1
4
0
2
Order By: Relevance
“…The same authors also support another factor that may have favored this result, which is the leaf presence in the cuttings, since they continue the process of production and supply of carbohydrates used in the rhizogenic process. Similar results were found by Valmorbida and Lessa (2008), who also observed that there was no effect of IBA and boron on rooting percentage of ginkgo tree cuttings (Ginkgo biloba). Furthermore, for the same azalea genus, Salvador, Jadoski and Resende (2005) observed that there was no effect of IBA on rooting percentage of Rhododendron indicum cuttings.…”
Section: Statistical Analysis Of Iba and Boron Application On Otto Ansupporting
confidence: 87%
“…The same authors also support another factor that may have favored this result, which is the leaf presence in the cuttings, since they continue the process of production and supply of carbohydrates used in the rhizogenic process. Similar results were found by Valmorbida and Lessa (2008), who also observed that there was no effect of IBA and boron on rooting percentage of ginkgo tree cuttings (Ginkgo biloba). Furthermore, for the same azalea genus, Salvador, Jadoski and Resende (2005) observed that there was no effect of IBA on rooting percentage of Rhododendron indicum cuttings.…”
Section: Statistical Analysis Of Iba and Boron Application On Otto Ansupporting
confidence: 87%
“…Trabalhos conduzidos por Scalon et al (2003), testando o efeito dos tratamentos água, ácido indol acético (ANA), ANA+boro, AIB, AIB + boro e boro no enraizamento de estacas de alecrim, constataram que o comprimento da maior raiz (11,5 cm) foi obtido com AIB (250 mg/L) + boro (100 mg/L), no mês de agosto. O boro adicionado à auxina tem como função proporcionar aumento na formação e crescimento das raízes (Valmorbida & Lessa, 2008).…”
Section: Resultsunclassified
“…Contudo, algumas espécies como kiwi (Ono et al, 1995), Platanus acerifolia (Nicoloso et al, 1999) e Ginkgo biloba (Valmorbida & Lessa, 2008) têm pequena resposta ou não respondem à aplicação de boro isolado e/ou em conjunto com reguladores vegetais auxínicos no que tange ao desenvolvimento radicular.…”
Section: Fonte De Variaçãounclassified